Intervention to Improve Children’s Hygiene in Urban Squatter Settlement Schools in Pakistan: An Implementation Research - Nousheen Akber Pradhan; Muzna Hashmi; Laraib Mazhar; Muhammad Uzair; Laeba Hussain; Maleeha Naseem; Shagufta Iqbal; Tazeen Saeed Ali; Rozina Karmaliani; Fauzia Basaria Hasnani (Environmental Health Insights)
Background: School-based interventions are crucial for promoting healthy behaviors in children and preventing the spread of diseases. This study aimed to enhance hygiene knowledge and practices (K&P) among school children through a school-based intervention. Objective: To improve personal and environmental hygiene K&P amongst primary and middle-grade students in urban squatter settlement schools in Karachi, Pakistan using school-based intervention. Design: Quasi-experimental study conducted in three schools over 2 years. Setting: Urban squatter settlement schools in Karachi, Pakistan, serving primary, and middle-grade students. Participants: A total of 156 students participated in the study, with a majority of 55.77% being girls (n = 87). Pre- and post-intervention assessments were conducted to evaluate the impact of the intervention. Intervention: Behavioral Change Communication (BCC) strategies aimed at improving school children’s hygiene K&P. Primary Outcome Measures: The primary outcome measures included changes in hygiene K&P pre- and post-intervention, specifically focusing on personal hygiene and environmental hygiene. Results: Significant improvements observed post-intervention. Mean knowledge score differences were 20.33 (SD = 5.85) for personal hygiene and 10.08 (SD = 7.72) for environmental hygiene. Practice scores also increased, with mean differences of 2.52 (SD = 1.98) and 2.47 (SD = 2.08) for personal and environmental hygiene, respectively. Statistically significant improvements (P < .05) were noted across most of the hygiene domains. Conclusions: The school-based intervention effectively improved personal and environmental hygiene K&P among primary and middle-grade children in urban squatter settlement schools. Key recommendations include integrating hygiene education into the curriculum, providing enabling environment to children and capacity building of school teachers to teach hygiene education.